2016
DOI: 10.1017/s0022215116007155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Tympanogram Width (Tw) with Adenoid Hypertrophy: Predictor of Otitis Media with Effusion Occurance in Adenoid Hypertrophy

Abstract: Objectives: To review the literatures, it is still a controversy about different materials to take rate in tympanoplasty. This study aims to investigate the anatomical and outcomes of Transcanal Endoscopic tympanoplasty with different donor sites of grafts. Objective: To review the literatures, it is still a controversy about different materials to take rate in tympanoplasty. This study aims to investigate the anatomical and outcomes of Transcanal Endoscopic tympanoplasty with different donor sites of grafts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This result is in accordance with a study conducted by Wahyudiono and Halim, who obtained a significant correlation between true lateral radiography-based A-N ratio and Tw in adenoid hypertrophy patients ( p < 0.01). 13 The study of Nwosu et al showed a significant correlation between adenoid hypertrophy and middle-ear disorders in children aged 1 to 10 years ( p < 0.05). 3 A study conducted by Kiama also obtained a significant correlation between adenoid hypertrophy and the incidence of middle-ear disorders in children aged 1 to 8 years ( p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This result is in accordance with a study conducted by Wahyudiono and Halim, who obtained a significant correlation between true lateral radiography-based A-N ratio and Tw in adenoid hypertrophy patients ( p < 0.01). 13 The study of Nwosu et al showed a significant correlation between adenoid hypertrophy and middle-ear disorders in children aged 1 to 10 years ( p < 0.05). 3 A study conducted by Kiama also obtained a significant correlation between adenoid hypertrophy and the incidence of middle-ear disorders in children aged 1 to 8 years ( p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…This result is in accordance with a study conducted by Wahyudiono and Halim, who obtained a significant correlation between true lateral radiography-based A-N ratio and Tw in adenoid hypertrophy patients (p < 0.01). 13 The study of Nwosu et al showed a significant correlation between adenoid hypertrophy Adenoid-Nasopharyngeal Ratio and Tympanogram Width Utama et al…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation